Pengaruh Koordinasi Terhadap Kualitas Pelayanan Izin Mendirikan Bangunan Apartemen Pada Dinas Penanaman Modal Pelayanan Terpadu Satu Pintu Kota Bandung - Wendi Wardhana (Scientia Regendi, 2020)
The purpose of this research was to determine and analyze the magnitude of the effect of coordination on the quality of service on the Permit for Building Apartments in the Investment Office and the One Stop Services in Bandung City. The research method used in this research was descriptive and explanatory survey methods with a sample of 53 respondents, and the data analysis method used was path analysis using the SPSS version 20 data processing application software.Based on the results of the research found that coordination has a positive and significant effect on service quality with a coefficient of determination of 70.20%, while 29.80% is influenced by factors outside the coordination variable. The managerial implication of this research is to improve the quality of services in the Office of Investment and Integrated Services of the One Door of the City of Bandung by increasing coordination between the Office of Investment and Services of the One Door Integrated with other related Offices in the City of Bandung. Other managerial implications are that the Office of Investment and Integrated Services of the One Door of the City of Bandung must pay attention and improve several coordination indicators such as the level of ability to develop service products, the accuracy of service information, the accuracy of human resources, the accuracy of the technology used, and the level of frequency of research and development activities.